Evaluation of inflammatory and immune responses in long-term cultured human precision-cut lung slices - Angela Temann; Tatiana Golovina; Vanessa Neuhaus; Carolann Thompson; Jessica A. Chichester; Armin Braun; Vidadi Yusibov (Taylor & Francis Group, 2017)
The development of systems that are more accurate and time-efficient in predicting safety and efficacy of target products in humans are critically important in reducing the cost and duration of pharmaceutical development. To circumvent some of the limitations imposed by the use of animal models, ex vivo systems, such as precision-cut lung slices (PCLS), have been proposed as an alternative for evaluating safety, immunogenicity and efficacy of vaccines and pharmaceuticals. In this study, we have established a human PCLS system and methodology for PCLS cultivation that can provide long-term viability and functionality in culture. Using these techniques, we found that cultured PCLS remained viable for at least 14 d in culture and maintained normal metabolic activity, tissue homeostasis and structural integrity. To investigate whether cultured PCLS remained functional, lipopolysaccharide (LPS) was used as a target stimulating compound. We observed that after an 18-hour incubation with LPS, cultured PCLS produced a set of pro-inflammatory cytokines, including TNF-α, IL-1β, IL-6 and IL-10 as well as the enzyme COX-2. Furthermore, cultured PCLS were shown to be capable of generating re-call immune responses, characterized by cytokine production, against antigens commonly found in routine vaccinations against influenza virus and tetanus toxoid. Taken together, these results suggest that human PCLS have the potential to be used as an alternative, high-throughput, ex vivo system for evaluating the safety, and potentially immunogenicity, of vaccines and pharmaceuticals.